Practice of "non-contact" nursing for COVID-19 close contacts based on FOCUS-PDCA mode (基于 FOCUS-PDCA模式的新型冠状病毒肺炎密切接触者"无接触式"护理实践) - KANG Hua (康铧); ZHANG Lei (张磊); ZHANG Lijun (张丽君); LI Ye (李野); TANG Ling (唐玲) (Journal of International Translational Medicine Limited, 2022)
Objective To explore the application of FOCUS-PDCA nursing mode in intensive medical observation points for COVID-19 close contacts and the effect of preventing and controlling epidemic situation. Methods FOCUS-PDCA nursing work mode was used to analyze the risk of infection among nurses. Combined with modern artificial intelligence technology, the implementation process of PDCA cycle was replaced with the "non-contact" implementation process. Results The centralized medical observation point operated for 25 days, and a total of 24 close contacts were treated. The nursing work was carried out successfully without infection, and the nursing quality was continuously improved. Conclusion The "non-contact" nursing practise based on FOCUS-PDCA mode can produce certain satisfactory effects. (目的 探讨FOCUS-PDCA护理工作模式在新型冠状病毒肺炎密切接触者集中医学观察点的应用及防控疫情的效果。方法 采用FOCUS-PDCA护理工作模式分析护理人员感染的风险问题, 与现代人工智能技术相结合, 将PDCA循环的实施过程改进为"无接触式"实施过程。结果 集中医学观察点运行25 d, 共收治24例密切接触者, 护理工作顺利开展, 无感染事件发生, 持续提高护理质量。结论 采用基于FOCUS-PDCA 的"无接触"护理工作模式, 效果较好, 值得借鉴。)